Investigation into channel angular extrusion and the UREAD energy absorption technique - LUPOI, ROCCO (My University, 2008)
Channel Angular Extrusion(CAE) processes are characterised by imposing high level of strain into deformable materials using simple tools where the material is contained within a specific path. Tool stresses could be critica l. The process is capable of reducing the thickness of flat sheets or slabs, and using Equal Channels, it could be used for material refinement where internal grain size changes to nano - scale structure by intense shearing. In this paper, the applicati ons of CAE have been extended to include the construction of Universal Re - useable Energy Absorption Devices (UREAD) using equal channels. An investigation is carried out into the distribution of contact stresses at the tool/material interface. The m odel employs the slab method of analysis and splits the material inside the channels, which intersects at 90 ̊ , into two zones; one causes the deformation while the other remains rigid. Normal stresses that may develop at the contact surface between the deformable material and the tools are analysed for various cases of CAE and are compared with those obtained by the Finite Element Analysis. Experimental investigation on UREAD devices using lead are also presented where the energy absorbed reached a m aximum of 160 J for 100mm cross sectional area and 30mm stroke. An experimental set up for measuring contact pressure in CAE/ECAE is introduced and measurements at different depth of the CAE entry channel are presented. The sensing mechanism is based upon the sensitive pressure pin technique.
PUBLISHED
Keywords: pressure pin technique; contact stresses; Stress analysis; UREAD; energy absorption; ECAE; CAE